ANALYSIS OF MILLENNIAL CONSUMER BEHAVIOR IN THE 4.0 ERA IN MEDAN CITY - Ayu, Ade Rahma (Jurnal Manajemen, 2025)
In this era of rapid technological development and the rapid dissemination of information. This greatly influences the patterns and lifestyles of almost all people, especially generations millennial. The development of the cafe business as a form of micro and small and medium enterprises (MSME’s) in the city of Medan is dominated by young people millennial generation. The facilities provided by the cafe include free wifi and a unique interior favored by visitors among millennials. Consumer style behavior of today's generation of children (millennials and z) in this digital era has both positive and negative impacts. From the proliferation of cafe businesses can increase employment opportunities in the city of Medan. With the consumer style behavior of the millennial and z generations can increase independent entrepreneurial innovation young people in Indonesia, especially in the city of Medan. Based on research results, Lifestyle The millennial and z generations are a very influential factor in the development of the cafe business in the city of Medan. The millennial and z generations also prefer cafes that have interior design which is instagrammable. Through several processes that are not easy, cafe owners can develop its business in a competitive market in the city of Medan